Third Five Year Plan Selected Physical Targets Agriculture and Irrigation Madras State - Planning Commission (Planning Commission, 1961)
Coverage of Community Development Blocks, Estimates of Gross Area Sown Under Main Crops, Proposed Outlays In the Third Plan, Summary Statement of Areas Benefited and Additional Production of Foodgrains, Detailed Statement Showing the Yardsticks and Estimated Production of Oil Seeds, Summary Statement of Special Developmental Measures For Principal Crops Other Than Food Grains, Summary Statement of Special Developmental Measures For Principal Crops Other Than Foodgrains—Cont., Summary Statement of Special Developmental Measures For Principal Crops Other Than Foodgrains—Cont., Major and Medium Irrigation, Flood Control, Etc.
Finance (Planning and Development) Department Government of Madras